Magnetically triggered thermoelectric heterojunctions with an efficient magnetic-thermo-electric energy cascade conversion for synergistic cancer therapy - Xue Yuan; Yong Kang; Ruiyan Li; Gaoli Niu; Jiacheng Shi; Yiwen Yang; Yueyue Fan; Jiamin Ye; Jingwen Han; Zhengcun Pei; Zhuhong Zhang; Xiaoyuan Ji (Nature Communications)
Abstract Thermoelectric therapy has been emerging as a promising and versatile strategy for targeting malignant tumors treatment. However, the lack of effective time-space controlled triggering of thermoelectric effect in vivo limits the application of thermoelectric therapy. Here a magnetically triggered thermoelectric heterojunction (CuFe2O4/SrTiO3, CFO/STO) for synergistic thermoelectric/chemodynamic/immuno-therapy is developed. The efficient magnetothermal nanoagent (CFO) is synthesized using the hydrothermal method, and thermoelectric nanomaterials (STO) are grown on its surface to create the heterojunction. To enhance oral delivery efficiency, a fusion membrane (M) of Staphylococcus aureus and macrophage cell membranes are coated the CFO/STO heterojunction, enabling effective targeting of orthotopic colorectal cancer. Once the CFO/STO@M reaches the tumor region, in vitro alternating magnetic field (AMF) stimulation activates the catalytic treatment through a magnetic-thermo-electric energy cascade conversion effect. Additionally, the immunogenic death of tumor cells, down-regulating vascular endothelial growth factor and heat shock protein HSP70, increasing expression of endothelial cell adhesion molecule (ICAM-1/VCAM-1), and M1 polarization of macrophages contribute to tumor immunotherapy. Overall, the magnetically triggered thermoelectric heterojunction based on CFO/STO@M shows remarkable antitumor capability in female mice, offering a promising approach to broaden both the scope of application and the effectiveness of catalytic therapy.